The Influence Of Digital Competence, Teamwork, And Emotional Intelligence On Lecturer Performance: A Study Of Management Department Lecturers - Dwi Kristanto; Justin Bongsoikrama; Pambuko Naryoto; Hasan Ipmawan; Maruji Pakpahan; Aris Wahyu Kuncoro (Jurnal Ilmiah Multidisiplin, 2025)
The advancement of technology and the increasing complexity of tasks in higher education demand lecturers to possess digital competence, effective teamwork capabilities, and emotional intelligence to support optimal performance. However, the implementation of these three factors continues to face various challenges in practice. This study aims to analyze the influence of digital competence, teamwork, and emotional intelligence on lecturer performance within the Management Study Program at Universitas Budi Luhur Jakarta. Adopting a quantitative approach, this study involved the entire population of 39 lecturers using a saturated sampling technique. Data were collected through questionnaires and analyzed using Partial Least Squares (PLS) to examine the relationships among variables. The results indicate that digital competence has a positive and significant impact on teaching effectiveness, research, and community service. Emotional intelligence also demonstrates a significant effect through the ability to manage emotions and build conducive relationships. Furthermore, teamwork contributes positively by enhancing synergy, effective task distribution, and a harmonious work environment. These findings highlight the importance of developing digital competence, emotional intelligence, and teamwork as foundational pillars for improving lecturer performance in a holistic and sustainable manner